1996
DOI: 10.1152/jn.1996.76.1.471
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of treadmill locomotion in adult cats before and after spinal transection

Abstract: 1. The aim of this study was to document the kinematics and the electromyographic activity recorded from several muscles during treadmill locomotion in the same cat (N = 4), before and after spinalization by using a chronic implantation method. Because identical experimental and control conditions were used, it was possible to establish similarities and differences in the timing and amplitude of the muscular activity and kinematics under the intact and spinal conditions in the same animal. The data presented i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
164
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(180 citation statements)
references
References 0 publications
16
164
0
Order By: Relevance
“…For instance, there was a burst of activity in both Srt, a hip flexor/knee extensor, during stance that was not observed in the intact state. Such an activation of Srt during stance is commonly observed after a complete spinal transection during locomotion on a level surface (Bélanger et al, 1996). In addition the bursting activity of Srt bilaterally was slightly asymmetric, the flexor burst observed in the intact state remained on the right side, but was absent on the left side.…”
Section: Treadmill Training Improvement Of Spinal Locomotionmentioning
confidence: 68%
“…For instance, there was a burst of activity in both Srt, a hip flexor/knee extensor, during stance that was not observed in the intact state. Such an activation of Srt during stance is commonly observed after a complete spinal transection during locomotion on a level surface (Bélanger et al, 1996). In addition the bursting activity of Srt bilaterally was slightly asymmetric, the flexor burst observed in the intact state remained on the right side, but was absent on the left side.…”
Section: Treadmill Training Improvement Of Spinal Locomotionmentioning
confidence: 68%
“…Before clonidine injection, rhythmic bursts of ENG activity were scarcely evoked by perineal stimulation Bélanger et al, 1996) in shams (two of seven cats) (Fig. 5a).…”
Section: Training and Fictive Locomotionmentioning
confidence: 99%
“…Previous studies first demonstrated this beneficial effect in adult spinal cats that have a remarkable capacity to recover locomotion (Lovely et al, 1986;Bélanger et al, 1996;De Leon et al, 1998). Moreover, clonidine, an ␣-2 noradrenergic agonist, improves and accelerates the recovery of stepping early after spinalization in cats (Forssberg and Grillner, 1973;Barbeau and Rossignol, 1991;Chau et al, 1998) and, when combined with treadmill training, improves walking patterns in SCI humans (Fung et al, 1990;Rémy-Néris et al, 1999).…”
Section: Introductionmentioning
confidence: 96%
“…[125][126][127] In humans, gait training may promote synapse formation in the CPG. There is evidence in animals [125][126][127][128][129] and humans 120,[130][131][132][133][134][135][136][137] that such an approach is beneficial. It is also of interest that training is specific in that animals trained to stand eventually weight bear on the hindlimbs but do not step; likewise, step training produces the opposite effect.…”
Section: Clinical Implications Of Spinal Shockmentioning
confidence: 99%